The role of mnemonic devices in learning new vocabulary in middle school EFL classes - Komilbaeva , Mohiniso Nodirbek qizi; Sultonova , Maftuna Baxtiyorovna (The Lingua Spectrum, 2026)
This article analyzes the impact of using mnemonic devices in learning new vocabulary in middle school English classes. In modern education, effective vocabulary acquisition is an essential part of language learning, because students need a sufficient number of words to communicate, read, write, and understand English successfully. However, many learners find it difficult to remember new lexical items through traditional memorization methods. Therefore, teachers need to use more effective and student-centered techniques that help learners remember and apply new vocabulary more easily. The study focuses on how mnemonic techniques influence students’ participation, interest, and ability to acquire new lexical items during English lessons. It also examines how these methods support students in remembering, correctly using, and applying new vocabulary in practical communication. Mnemonic devices, such as associations, images, acronyms, rhymes, and keyword techniques, can make vocabulary learning more meaningful and memorable for students. During the research, mnemonic techniques are compared with traditional memorization methods, and their effectiveness is evaluated. The findings show that the use of mnemonic devices helps students acquire vocabulary faster and more effectively, while also increasing their classroom engagement and motivation. The results of the study highlight the importance of using mnemonic techniques in English language teaching and provide practical recommendations for organizing a more effective and interactive vocabulary learning process.